Original paperInvasive ductal carcinoma of no special type and its corresponding lymph node metastasis: do they have the same immunophenotypic profile? - Fulga, Veaceslav; Rudico, Lucian; Balica, Amalia Raluca; Cimpean, Anca Maria; Saptefrati, Lilian; Raica, Marius (Polish Journal of Pathology, 2015)
In the present study we compared the immunophenotypic subtypes of breast ductal invasive carcinomas with their ipsilateral, axillary lymph node metastasis. The ER (estrogen receptor), PR (progesterone receptor), Her2 (human epidermal growth factor receptor 2), and CK5 (cytokeratin 5) status and the proliferation marker Ki-67 were determined by immunohistochemistry on specimens from 43 women. All selected cases were diagnosed as invasive breast carcinomas, of no special type (NST), G2 grade of differentiation. The most frequently encountered subtype at both sites was luminal B. We determined that tumor profile evaluated by surrogate markers is not stable during the metastatic process. The total rate of shifted cases was 23.26% (10 cases), and the highest rate of shifting (6.98%) was encountered from luminal B/Ki-67 to luminal A subtype. In five cases, the subtype shifted to a poorer one according to prognosis. These data support the hypothesis that breast cancer is a heterogeneous disease, with substantial variability of cellular components within each category, a statement applicable to invasive breast carcinomas of NST type too. The receptor profile of this carcinoma, indicated by surrogate markers, is not stable throughout the metastatic process.